Manipulating the leaf area to fruit mass ratio alters the synchrony of total soluble solids accumulation and titratable acidity of grape berries. (3rd March 2015) - Parker, A.K.; Hofmann, R.W.; van Leeuwen, C.; McLachlan, A.R.G.; Trought, M.C.T.
Abstract: Background and Aims: This study investigated: (i) the importance of changing the leaf area: fruit mass ratio (LA : FM) by crop removal and/or shoot trimming on total soluble solids (TSS) concentration and content, pH, titratable acidity (TA) and berry mass; (ii) the extent to which changes in LA : FM ratio altered the synchrony TSS : TA ratio; and (iii) whether the responses were consistent for Pinot Noir and Sauvignon Blanc. Methods and Results: Vertical shoot positioned–trained vines were trimmed shortly after fruitset or at veraison to six or 12 main leaves per shoot and crop thinned by removing 0, 50 or 75% of the bunches. TSS and pH, TA and fresh berry mass were measured weekly from pre‐veraison to harvest. TSS concentration accumulation in berries was slowed with shoot trimming and accelerated by crop removal, with crop removal having a greater effect. Trimming shoots at fruitset in combination with no crop removal resulted in the greatest delay in veraison (the start of TSS accumulation) and slowest rate of TSS accumulation. TSS content mirrored TSS concentration for LA : FM manipulations at fruitset but fewer differences were detected for LA : FM changes at veraison. In contrast, TA and pH were largely unaffected. Conclusions: Changes to the LA : FM ratio via crop removal or shoot trimming modified berry TSS accumulation but not TA. Such desynchronisation was consistent for both cultivars. Significance of the Study: Crop and/or leaf removal represent valuable means to manipulate the time to achieve target fruit TSS concentration and TA. The similar responses of the two cultivars indicate that LA : FM manipulation could potentially have common responses for different cultivars. The desynchronisation of berry components highlights the need to consider each berry component individually and in a dynamic manner by sampling throughout the ripening phase.